2004
DOI: 10.1080/13691830410001682061
|View full text |Cite
|
Sign up to set email alerts
|

It depends… how organisational participation affects political participation and social trust among second‐generation immigrants in Denmark

Abstract: Tuinier, J. D., & Visser, G. (2013). Democratie onderzoeken in een Fort, een Fabriek en in een LAB: Achtergronden, doelen en uitgangspunten van de Interactieve Methodiek [Investigating democracy in a fortress, a factory and in a lab: Backgrounds, objectives and principles of an interactive methodology]. Utrecht, the Netherlands: Stichting Vredese-ducatie/Peace Education Projects. Retrieved from https://www .fortvandedemocratie.nl/ Van Bergen, D. D., Feddes, A. R., Doosje, B., & Pels, T. V. M. (2015).Collective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 9 publications
6
65
2
3
Order By: Relevance
“…These findings can mean that intragroup contact between immigrants should be encouraged, especially in the early stages of life in the new country. This runs contrary to earlier research in the Danish case that find no correlation between intra-group associational memberships and generalized trust among second generation immigrants (Togeby, 2004). Further evidence from Denmark suggests that public libraries are most successful in promoting integration when providing universal services rather than focusing upon the immigrants cultures of origin (Elbeshausen & Skov, 2004).…”
Section: Literature Reviewcontrasting
confidence: 55%
“…These findings can mean that intragroup contact between immigrants should be encouraged, especially in the early stages of life in the new country. This runs contrary to earlier research in the Danish case that find no correlation between intra-group associational memberships and generalized trust among second generation immigrants (Togeby, 2004). Further evidence from Denmark suggests that public libraries are most successful in promoting integration when providing universal services rather than focusing upon the immigrants cultures of origin (Elbeshausen & Skov, 2004).…”
Section: Literature Reviewcontrasting
confidence: 55%
“…In their study on Moroccans, Turks and Surinamese immigrants in Amsterdam, they found a correlation between the density of networks of their ethnic organisations and the degree of political participation at the group level. Organisational density, in this context, is an indicator of the degree of ethnic civic community (see further van Heelsum 2005 andVermeulen 2006). Thus, in this perspective, organisational networks reflect the amount of social capital at the group level: '[s]ocial capital at the group level is a function of (1) the number of organisations, (2) the variety in the activities of the organisations and (3) the density of the organisational network' (Tillie 2004, 531).…”
Section: Associational Involvement Social Capital and The Political mentioning
confidence: 99%
“…1 Our focus on Muslims is aimed to explore the interplay of the religious and the ethnic dimensions of social capital and therefore to dig deeper into the role of social capital for the political participation of immigrants. Recent works on the political participation of immigrants in Europe have focused on the role of associational involvement and social capital (Berger, Galonska, and Koopmans 2004;Eggert and Giugni 2010;Jacobs, Phalet, and Swyngedouw 2004;Morales and Giugni 2011;Tillie 2004;Togeby 2004). This body of works posits a link between involvement in voluntary associations and the political participation of immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to multi-ethnicity, multicultural and multi-religiosity of Malaysian citizens, which subsequently required tolerance value and behaviour, thus become the key factor for economic, political and social stability (Banton, 1985 Nizah, 2015), which becomes a huge task to maintains its harmony. Apart from it, scholars agreed that active participation in political activities may breed tolerance behavior (Chzhen, 2013;McClosky & Brill, 1983;Togeby, 2004). The divergence accounts on tolerance and participation become the main concern of this study.…”
Section: Introductionmentioning
confidence: 99%